LANGUAGE AND POWER IN A WTO DIRECTOR -GENERAL’S SPEECH - A CRITICAL DISCOURSE ANALYSIS - Mai Nga, Dang Thi (VNU Journal of Foreign Studies, 2020)
The paper is aimed at exploring ideological power relations of globalization discourse through the analysis of the speech ‘The Backlash against Globalization’ of WTO’ s Director-General Mike Moore based on one of the Discourse Analysis (DA) approaches - Critical Discourse Analysis (CDA). At first, the paper sets out the theoretical framework of CDA and the concepts of power and ideology and examines the importance of Systemic Functional Grammar (SFG) in CDA. Then the paper provides readers with the social context of globalization and analyzes the speech in the light of CD. The findings and the conclusion of the paper prove the assumption that the speech is a tool for Director-General Mike Moore to express his power and ideology in the sense that he is in higher position and confirms that globalization is inevitable and the establishment of WTO is a product of this process helping countries, communities and people face the problems and challenges.